INCREASING SCHOLARSHIP OPPORTUNITIES IN TAIWAN: TIPS AND TRICKS: MENINGKATKAN PELUANG BEASISWA DI TAIWAN: TIPS DAN TRIK - Devayana Putra, Cendra; Lavita Angelina, Clara (Darmabakti Cendekia: Journal of Community Service and Engagements, 2024)
Background: COVID-19 has significantly impacted education, resulting in low acceptance rates at universities in Taiwan and Indonesia. These low acceptance rates contribute to a shortage of human resources, which could have far-reaching consequences for the economy, education, health, and political stability. Nations with limited human capital may become dependent on foreign labor to meet their workforce needs, leading to local unemployment and heightened competition between local and foreign workers. Therefore, investing heavily in education and training is crucial. Objective: To address this issue, community services have been conducted in Indonesia to provide students with information on scholarships and technical strategies. Method: The community services were organized in several steps, including preparation, planning, implementation, and evaluation. Results: The effectiveness of the event was assessed through pre-test and post-test questionnaires. Conclusion: Through a series of scholarship webinars, it was observed that knowledge and awareness about scholarships increased, providing students with greater opportunities for securing scholarships.